Asthma due to aluminium soldering flux. Issue 6 (November 1967) - Sterling, G. M.
Abstract : Two patients have been studied who complained of dyspnoea after the inhalation of fumes from a new soldering flux recently developed for use in jointing aluminium which has been replacing copper as a material for electric cables. A previous survey of respiratory complaints after the use of this particular flux had failed to show any objective change in lung function, and the present cases are the first to be reported. Both subjects have been investigated by means of serial spirometry, peak flow rates, and body plethysmography following inhalation of small amounts of flux fumes; delayed and prolonged bronchoconstriction has been demonstrated. Similar results have been obtained after the inhalation of one of the main constituents of the flux, namely amino-ethyl ethanolamine, which is presumably the active allergic agent. The bronchial response is unusual in being delayed in onset but otherwise resembles pollen-sensitivity asthma rather than the infiltrative process seen in farmer's lung. The type of immune mechanism involved is speculative, but it is possible that some alteration of the amino-ethyl ethanolamine is needed before it can react with reaginic antibody fixed in the bronchial tissues.